A study on patient safety with reference to medication errors at a tertiary care hospital - Dake, Rajesh; Ramana, I. Venkata (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of this present study was to determine and evaluate the nature and types of medication errors (MEs) in a tertiary care hospital. Methods: This was a prospective, observational study was conducted on medication errors in a tertiary care hospital, Kakinada during January 2019 to December 2019. MEs were categorized as prescription error (PE), transcription error (TE), dispensing error (DE), and administration error (AE). The case records and treatment charts were reviewed. The one-way ANOVA test for independent measures was done for statistical analysis. Results: A total of 5792 patients were included during the study period. Total numbers of MEs were n=353 (6.10%). The most common ME was TEs n=191 (54%) followed by AEs n=117 (33%). Nursing errors n=316 were more compared to doctors’ errors n=18. The one-way Anova test for independent measures was done for statistical analysis; the f-ratio value is 6.44654. The p-value is 0.004332. The result is significant at p<0.05. Conclusions: There is a need to establish effective ME reporting system to reduce its incidence and improve patient care and safety. Regular trainings and interdepartmental sharing of facts on medication errors should be done at regular intervals.